Slavery in current films Django Unchained and 12 Years a Slave - Kňourková, Markéta (Univerzita Pardubice, 2017)
This bachelor thesis is focused on two current movies Django Unchained and 12 Years a Slave, which are both dedicated to American slavery in the nineteenth century, specifically two years before the Civil War. The aim of this thesis is to find and analyse four main elements racial stereotypes, slavery, freedom, and revenge. This paper also tries to prove that all these elements were not only closely related but also significantly influenced the lives of the slaves as well as their white slavers who had been involved in this inhumane institution.
Otroctví v současných filmech Nespoutaný Django a 12 let v řetězech
Keywords: Afro-Americans; Django Unchained; 12 Years a Slave; stereotype; freedom; slavery revenge; Afro-Americans; Django Unchained; 12 Years a Slave; stereotype; freedom; slavery revenge; Afroameričané; Nespoutaný Django; 12 let v řetězech; stereotyp; svoboda; otroctví; pomsta